2020
DOI: 10.1016/j.ausmj.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

To Donate or to Waste It: Understanding Posthumous Organ Donation Attitude

Abstract: The aim of this paper is to improve knowledge and foster a deeper understanding of various aspects of influencing posthumous organ donation. Extending the Theory of Reasoned Action this study integrates four external explanatory belief factors, altruism, perceived benefit, perceived risk and familial subjective norm to more fully explain organ donation intentions to sign a donor card. The data was gathered from a convenience sample of 423 via an online survey. The relationships between the constructs of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…In addition, the rise of sustainable products is being driven by marketing trends variously highlighting the importance of altruism (Alsalem et al, 2020; Hartmann et al, 2017), caring about others’ wellbeing (Hurst et al, 2013; Leonidou et al, 2015), and conservation of nature (McNeill & Moore, 2015; Tsai et al, 2020). In particular, encouraging such motives among consumers causes them to feel a “warm glow” (Hartmann et al, 2017; Iweala et al, 2019) when purchasing and consuming sustainable products because they are contributing to a good cause.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…In addition, the rise of sustainable products is being driven by marketing trends variously highlighting the importance of altruism (Alsalem et al, 2020; Hartmann et al, 2017), caring about others’ wellbeing (Hurst et al, 2013; Leonidou et al, 2015), and conservation of nature (McNeill & Moore, 2015; Tsai et al, 2020). In particular, encouraging such motives among consumers causes them to feel a “warm glow” (Hartmann et al, 2017; Iweala et al, 2019) when purchasing and consuming sustainable products because they are contributing to a good cause.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Concerning health care and medicine-related fields, for example, the study of organ donation after death [ 38 ] explored the attitude and intention of organ donation through rational behavior theory and explained the rational decision-making process of this behavior. Moreover, in the study of the condom use behavior of people living with HIV [ 39 ] it was found that the subjective norms of condom use in individual cases can significantly predict the possibility of condom use in future sex.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…On the other hand, it is a serious medical intervention and a possibly life-threatening event itself with far-reaching consequences for the individuals involved. There is research on transplantation-associated psychological factors of organ donors (see e.g., [2][3][4][5][6]) and on psychological factors associated with the procedure on the organ recipients' side as well (see e.g., [7][8][9][10]). Studies show that, in terms of psychological distress, the most frequently reported symptoms among organ recipients are anxiety symptoms (particularly fear of organ rejection, repeated surgery, and death) and symptoms of depression [11][12][13].…”
Section: Introductionmentioning
confidence: 99%